Genetic variability and heritability of acid-adaptive soybean promising lines - HERU KUSWANTORO (Society for Indonesian Biodiversity, 2017)
Abstract. Kuswantoro H. 2017. Genetic variability and heritability of acid-adaptive soybean promising lines. Biodiversitas 18: 378-382. Genetic variability and heritability are very important in a variety improvement. The high genetic diversity can increase the probability on obtaining a new superior variety, while heritability can accelerate the selection process. In acidic dry land, genetic variability is also needed in order to increase such probability. The objective of this study was to estimate the genetic variability of acid-adaptive soybean promising lines. Ten advanced soybean-promising-lines derived from Tanggamus Ã— Anjasmoro varieties crossing were used as the materials. Results showed that the characters of days to flowering, the number of branches plant-1, the number of reproductive nodes plant-1, 100 grains weight and grain yield had broad genetic variability, while days to maturity, plant height and the number of filled pods plant-1 had narrow genetic variability. Characters of days to flowering, days to maturity, the number of filled pods plant-1 and 100-grain weight showed high broad sense heritability; characters of a number of branches plant-1, and the number of reproductive nodes plant-1 had moderate broad sense heritability; and plant height and grain yield had low broad sense heritability. Characters with broad genetic variability and high heritability can be used as sources in soybean variety improvement. The positive correlation between number of branches plant-1 with number of reproductive nodes plant-1 and number of filled pods plant-1 were significant. Significant positive correlations were also found between number of reproductive nodes plant-1 with number of filled pods plant-1. Negative correlations were found between weight of 100 grains with number of reproductive nodes plant-1 and number of filled pods plant-1. Similarly, negative correlations were also found between days to flowering with grain yield. Negative correlation between days to flowering and grain yield suggests to develop variety with early days to flowering. Keywords: Acid soil, genetic variability, heritability, soybeanÂ